MRI features of pediatric atypical teratoid rhabdoid tumors and medulloblastomas of the posterior fossa - Hsin‐Wei Wu; Chia‐Hung Wu; Shih‐Chieh Lin; Chih‐Chun Wu; Hsin‐Hung Chen; Yi‐Wei Chen; Yi‐Yen Lee; Feng‐Chi Chang (Cancer Medicine, 2023)
Abstract Background Atypical teratoid rhabdoid tumor (AT/RT) occurs at a younger age and is associated with a worse prognosis than medulloblastoma; however, these two tumor entities are mostly indistinguishable on neuroimaging. The aim of our study was to differentiate AT/RT and medulloblastoma based on their clinical and MRI features to enhance treatment planning and outcome prediction. Methods From 2005–2021, we retrospectively enrolled 16 patients with histopathologically diagnosed AT/RT and 57 patients with medulloblastoma at our institute. We evaluated their clinical data and MRI findings, including lesion signals, intratumoral morphologies, and peritumoral/distal involvement. Results The age of children with AT/RT was younger than that of children with medulloblastoma (2.8 ± 4.9 [0–17] vs. 6.5 ± 4.0 [0–18], p < 0.001), and the overall survival rate was lower (21.4% vs. 66.0%, p = 0.005). Regarding lesion signals on MRI, AT/RT had a lower ADCmin (cutoff value ≤544.7 × 10−6 mm2/s, p < 0.001), a lower ADC ratio (cutoff value ≤0.705, p < 0.001), and a higher DWI ratio (cutoff value ≥1.595, p < 0.001) than medulloblastoma. Regarding intratumoral morphology, the “tumor central vein sign” was mostly exclusive to medulloblastoma (24/57, 42.1%; AT/RT 1/16, 6.3%; p = 0.007). Regarding peritumoral invasion on T2WI, AT/RT was more prone to invasion of the brainstem (p < 0.001) and middle cerebellar peduncle (p < 0.001) than medulloblastoma. Conclusions MRI findings of a lower ADC value, more peritumoral invasion, and absence of the “tumor central vein sign” may be helpful to differentiate AT/RT from medulloblastoma. These distinct MRI findings together with the younger age of AT/RT patients may explain the worse outcomes in AT/RT patients.